2021
DOI: 10.3389/fimmu.2021.663843
|View full text |Cite
|
Sign up to set email alerts
|

Residual Viremia Is Linked to a Specific Immune Activation Profile in HIV-1-Infected Adults Under Efficient Antiretroviral Therapy

Abstract: Chronic immune activation persists in persons living with HIV-1 even though they are aviremic under antiretroviral therapy, and fuels comorbidities. In previous studies, we have revealed that virologic responders present distinct profiles of immune activation, and that one of these profiles is related to microbial translocation. In the present work, we tested in 140 HIV-1-infected adults under efficient treatment for a mean duration of eight years whether low-level viremia might be another cause of immune acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Whiskers represent the lowest and highest observations within the region defined by the limits Q1 -1.5 × IQR and Q3 + 1.5 × IQR. IL-6, interleukin 6; sCD14, soluble CD14 explanation could be derived from previous observations where incomplete ART adherence has been associated with residual viral replication [32,33], and where residual viral replication has been linked to heightened systemic inflammation [34][35][36]; however, other studies have not confirmed these findings [37,38]. Another possible driver of this association is that PWH who are not fully adherent to ART are more likely to accumulate risk factors and/or comorbidities that are also associated with high inflammation, immune activation and/or coagulopathy such as diabetes mellitus or chronic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Whiskers represent the lowest and highest observations within the region defined by the limits Q1 -1.5 × IQR and Q3 + 1.5 × IQR. IL-6, interleukin 6; sCD14, soluble CD14 explanation could be derived from previous observations where incomplete ART adherence has been associated with residual viral replication [32,33], and where residual viral replication has been linked to heightened systemic inflammation [34][35][36]; however, other studies have not confirmed these findings [37,38]. Another possible driver of this association is that PWH who are not fully adherent to ART are more likely to accumulate risk factors and/or comorbidities that are also associated with high inflammation, immune activation and/or coagulopathy such as diabetes mellitus or chronic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Detectable viral load and low CD4 count emerged in the two largest studies as having a deleterious effect on AMH, raising a question as to whether immune activation may act as a mechanism to decrease ovarian reserve [16,19]. As both HIV viremia and low CD4 tend to be accompanied by states of immune activation [32,33], these findings present the possibility of inflammation playing a pivotal role in ovarian aging. Recent evidence has linked decreased ovarian reserve and pathologic imbalances of proinflammatory and anti‐inflammatory cytokines [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low level viremia (LLV) has emerged as another biomarker of HIV persistent replication although its definition varies across studies due to differences in RNA-HIV quantification methods. Previous studies have reported an association between LLV, defined as an HIV-RNA VL between 1 and 20 copies/mL, higher levels of pro-inflammatory biomarkers (i.e., d-dimer, soluble CD163, soluble endothelial protein C receptor) [55,56], a larger HIV latent reservoir size [57] and a higher risk for non-AIDS events or death [58]. Moreover, contradictory results have been reported regarding whether LLV may be different between PI-based and DTG-based 3DRs [57,[59][60][61].…”
Section: Low-level Hiv Replicationmentioning
confidence: 98%